Laparoscopic Repair of a Large Paraesophageal Hernia with Migration of the Stomach into the Mediastinum Creating an Upside-Down Stomach - Nasser Sakran; Hadar Nevo; Ron Dar; Asnat Raziel; Dan Hershko (Case Reports in Surgery)
Upside-down stomach is a relatively rare type of a large paraesophageal hernia characterized by the migration of the stomach into the posterior mediastinum. Upside-down stomach is prone to severe complications and therefore surgery is recommended even in asymptomatic patients. A 62-year-old male presented with frequent abdominal pain with nausea and vomiting that persisted for one year. The patient was obese with fatty liver and was treated medically for gastroesophageal reflux disease (GERD) for 4 years. On upper gastrointestinal CT study a level-IV paraesophageal hernia was detected with upside-down stomach, and he was referred for elective surgery. Laparoscopic surgery included reduction of the stomach into the abdominal cavity followed by dissection of the paraesophageal membrane and hernia sac. The hiatal defect was closed using a wound closure device and nonabsorbable sutures. The defect closure was reinforced using Physiomesh tucked anteriorly and sutured posteriorly to the diaphragm. Follow-up was uneventful and the patient is free of complaints. The results of this surgical intervention support previous reports that laparoscopic repair with the use of biological mesh in the setting of large paraesophageal hernia should be favorably considered.